Information Release Through Internet: Empirical Evidence Towards a Company True and Fair View - Lopes, I. T. (Proceedings of the 5th International Conference on Intellectual Capital and knowledge Management and Organisational Learning, 2008)
: The dynamic processes of knowledge capture, transformation and dissemination, inside the companies, had drastically transformed the traditional strategic approaches. Information dissemination to multiple stakeholders had also changed the old market rules. These paradigms traditionally based on land and intensive workforce has been replaced by the electronic information power which crosses the entire management cycle. Information and communication technologies have revolutionized the old concepts of time and space. Broadly, new capabilities were introduced in the organisational systems. Internet, as the main dynamic electronic platform, has emerged as the way to easily reach several stakeholders’ information needs. Which type of data and information should companies release to their stakeholders? Should companies set up a borderline in the information dissemination chain? Based on the Portuguese biggest 500 companies, we have explored the typology of information effectively released to stakeholders through their corporate Web sites. A sample of 144 companies was extracted and a Web site content analysis was performed during the fourth quarter of 2007. Most of the companies use the Internet to share information with their stakeholders, although in some cases in accordance with financial market regulator rules. That information includes financial and corporate governance reports, periodical press releases, environmental and sustainability status. Otherwise, we also tried to explore and evidence the genesis of an Electronic Knowledge Management Culture (EKMC) for the Portuguese companies based on several capabilities implemented through their Web sites and based on the effective contribution and linkage with their stakeholders. Size of companies and financial performance indicators seems to contribute positively for the quality and quantity of information effectively disseminated (a positive and significant correlation was obtained). However, Web sites contents change on a systematic manner and those information repositories tend to reach only particular commercial needs. Capabilities identified are those that, from our understanding better describe the information release State-of-the Art. Web sites, as dynamics electronic platforms, should be contextualized in a particular time and space, strongly managed according particular internal and legal information rules. As evidenced, new capabilities should be introduced and performance rates require a continuous sustainable increase.